2012
DOI: 10.1161/strokeaha.111.636894
|View full text |Cite
|
Sign up to set email alerts
|

Near Infrared Spectroscopy for the Detection of Desaturations in Vulnerable Ischemic Brain Tissue

Abstract: Background and Purpose-There is uncertainty whether bilateral near infrared spectroscopy (NIRS) can be used for monitoring of patients with acute stroke. Methods-The NIRS responsiveness to systemic and stroke-related changes was studied overnight by assessing the effects of brief peripheral arterial oxygenation and mean arterial pressure alterations in the affected versus nonaffected hemisphere in 9 patients with acute stroke. Results-Significantly more NIRS drops were registered in the affected compared with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(12 citation statements)
references
References 5 publications
(5 reference statements)
1
10
0
Order By: Relevance
“…There was no interhemispheric difference between the maximum increases (p ¼ 0.189) or the maximum decreases (p ¼ 0.053). However, this result suggested a trend toward a potential difference between hemispheres, as it has been previously found by NIRS-DOS, 25,26 as mentioned in Sec. 1.…”
Section: Resultssupporting
confidence: 74%
See 1 more Smart Citation
“…There was no interhemispheric difference between the maximum increases (p ¼ 0.189) or the maximum decreases (p ¼ 0.053). However, this result suggested a trend toward a potential difference between hemispheres, as it has been previously found by NIRS-DOS, 25,26 as mentioned in Sec. 1.…”
Section: Resultssupporting
confidence: 74%
“…Fluctuations of cerebral hemodynamics have previously been observed in acute stroke patients. A study of nine patients with acute stroke 25 reported arterial desaturations from unknown origin that correlated with cerebral hemodynamics measured with near-infrared diffuse optical spectroscopy (NIRS-DOS), and showed an asymmetry of the changes in the two cerebral hemispheres. Pizza et al 26 observed in seven patients with acute/subacute middle cerebral artery stroke that obstructive and central apneas were linked to cerebral oxygenation changes by NIRS-DOS.…”
Section: Introductionmentioning
confidence: 99%
“…Current pilot studies are underway investigating this noninvasive method of monitoring patients in and around the early post-stroke period. [21] It may be potentially feasible for near-infrared technology to be used in the evaluation of large volume ischemic stroke and adapted for prehospital stroke evaluation. Small, mobile probes could 1 day be incorporated into all emergency medical vehicles and serve as a cost-effective screening tool without the need for CT scanners built into every ambulance.…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, there is a continuing effort to develop optical methods that can more directly target key cerebral parameters such as CBF and cerebral oxidative metabolism 25, 26 . DCE NIRS is one such approach and has been previously used to detect CBF abnormalities in stroke patients 15, 27 and in animal models of cerebral ischemia 16 . The work presented in this study extends the potential clinical utility of NIRS by presenting a DCE method of assessing BBB integrity.…”
Section: Discussionmentioning
confidence: 99%